Factors affecting the mathematics learning outcome of underachieving students at Colleges of Education - Kumah , Maxwell Seyram; Wonu, Nduka (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
The performance of a student in school is important to the educational system for making informed decisions about the progress of the students. However, there are many instances where students face challenges that influence their performance in Mathematics at all levels of education. This study, therefore, narrowed down on the perceived factors that affect student Mathematics performance at Colleges of Education. The analytic descriptive survey design was employed. The population of the study was all the 240 level 100 students from three programmes of study at a College of Education in the Hohoe municipality, Ghana. A total of 103 students participated in the study. Krajcie and Morgan (1970) formula was applied to estimate the sample size of the study. A diagnostic approach was used to identify the underachieving students with grades of C5 and C6 on entry into College from Senior High Schools (SHS) for inclusion in the study. A 20-item instrument titled “Learning Factors Scale (LFS)” and student end-of-semester Mathematics results were used for data collection. The LFS was validated by experts in Mathematics Education and the reliability test was computed using the Cronbach Alpha formula which yielded a value of 0.84. Data were analyzed using percentage distribution, Relative Importance Index (RII) and ranking (Rk). The aim was to determine which of the four factors explored, viz: Student-related Factors(SRF), Tutor-related Factors(TRF), Parent-related Factors (PRF) and College-related Factors(CRF) mostly affected the learning outcomes of the students in College Mathematics. The result shows that CRF was ranked as the most significant factor affecting student performance in Mathematics among the four factors. This was followed by PRF, SRF and TRF in that order. The result further showed that the factors respectively had weak and inverse relationships with the performance of the students in Mathematics. It was recommended among others that attention should be given to the four factors in teaching and learning Mathematics at College, especially CRF and PRF.